2014
DOI: 10.2478/intag-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Inputs on Strength and Stability of Soil Aggregates Under Rice-Wheat Rotation

Abstract: A b s t r a c t. The study aims to elucidate the impact of organic inputs on strength and structural stability of aggregates in a sandy loam soil. Tensile strength, friability and water stability of aggregates, and the carbon contents in bulk soil and in large macro (>2 mm), small macro (0.25-2 mm), micro (0.053-0.25 mm) and silt+clay size (<0.053) aggregates were evaluated in soils from a long-term experiment with rice-wheat rotation at Modipuram, India, with different sources and amounts of organic C inputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…The capillary-wetted soil aggregates did not show any clear trends across the treatments. Das et al, (2014) observed that a large reduction (50-75%) in MWD was observed upon slaking, more in case of inorganic N treatments. Variation in MWD of capillarywetted aggregates was also less (3.5-4.5 mm).…”
Section: Water Stable Aggregates (Wsa)mentioning
confidence: 89%
See 4 more Smart Citations
“…The capillary-wetted soil aggregates did not show any clear trends across the treatments. Das et al, (2014) observed that a large reduction (50-75%) in MWD was observed upon slaking, more in case of inorganic N treatments. Variation in MWD of capillarywetted aggregates was also less (3.5-4.5 mm).…”
Section: Water Stable Aggregates (Wsa)mentioning
confidence: 89%
“…Song et al, (2016) reported that compared to conventional tillage, the percentages of >2mm macro aggregates and water-stable macroaggregates in rice-wheat double-conservation tillage (zero-tillage and straw incorporation) were increased 17.22% and 36.38% in the 0-15 cm soil layer and 28.93% and 66.34% in the 15-30 cm soil layer, respectively. In surface soil (0-15cm), the maximum proportion of total aggregated carbon was retained with 0.25-0.106mm aggregates, and rice-wheat double-conservation tillage had the greatest ability to hold the organic carbon (33.64g kg −1 ) it is evident that the MBC contents in both surface and sub-surface soil were significantly higher in plots receiving 50% RDN as CF+50% RDN as FYM ( F 5 ) Aggregate-associated organic carbon Das et al, (2014) revealed that the long term application of organics increased aggregate associated C as compared in all aggregate size fractions; the highest increase was observed in plots receiving NPK and FYM in combination. Arthur et al, (2012) also indicate that post-tillage consolidation of soils developing into compact and denser aggregates is significantly reduced through addition of organic inputs.…”
Section: Aggregation and Structural Indicesmentioning
confidence: 92%
See 3 more Smart Citations